Crystal structures and pressure-induced phase transformations of LiAlH4: A first-principles study - Ukrit Keyen (2020)
© 2020 Author(s). Given the fact that lithium aluminum hydride (LiAlH4) can exist in distinct crystalline structures under different conditions, in this study, we aim to theoretically investigate the structural properties and the pressure-induced phase transformations of its 13 closely related crystal structures by means of the density functional theory (DFT). The present study reveals that the phase transformation of LiAlH4 from the most stable form (α-phase) to the second most stable form (-phase) occurs at approximately 3.3 GPa, corresponding to a volume collapse of ∼14% and a reduction of 22% in the crystal volume. Due to the relatively higher hydrogen weight content, -LiAlH4 becomes a potentially attractive candidate for solid-state hydrogen storage at moderate pressures. The two most stable forms, i.e., the structures with the (i) P21/c (α-LiAlH4) and (ii) I41/a (-LiAlH4) space groups, have been selected so that their structural and electronic properties can be discussed in greater detail. Our study also shows that the numerical results are greatly influenced by the choice of the DFT methods used, such as the exchange-correlation functionals and optimization schemes.